TRITUNGGAL: KONTROVERSI TEOLOGIS DAN IMPLIKASINYA BAGI IMAN KRISTEN - Tampubolon, Samuel (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2024)
The doctrine of the Trinity is one of the theological issues that is full of controversy until today, starting from the era of the church fathers to the contemporary era. It must be recognized that is impossible for the Trinity to be discussed and understood completely by limited human thought. This study aims to revitalize the doctrine of the Trinity in the midst of the rampant debate on social media, especially on the Youtube platform, which certainly creates an uncomfortable atmosphere. There are certain groups that vigorously reject the doctrine of the Trinity but claim to be Christians and their churches are legally recognized. The author will review the early history of the doctrine of the Trinity and examine its theological foundation to confront groups that oppose the doctrine of the Trinity. Althought the Bible literally does not write the term Trinity, the church and tradition contain it. A misunderstanding of God’s existences will also indirectly relate to and have an impact on other doctrines. The rejection pf the doctrine of the Trinity harms Christianity.